Propostas de modelagem matemática para o problema de restauração de sistemas de distribuição de energia elétrica radiais - Souza, Eliane Silva de [UNESP] (2014)
This work presents proposals of mathematical modeling to optimize the restoration problem of radial distribution electrical systems. The restoration problem consists in strategies of topological reconfiguration of the electrical network for optimal restoration of the electric energy supply to outage areas. The main objective is to supply the most possible demand of the system under the restorative state, preserving the physical and operational constraints of the electrical network, satisfying the criteria of quality and reliability of provided service. The problem has been solved for many decades by heuristic methodologies, with the meta- heuristics as the most used techniques. In the specialized literature there are no proposals for mathematical modeling to exact solving of the restoration problem through classical optimization techniques. The main reason was the lack of an efficient way to represent the radiality constraint through simple algebraic relations. Recently, a representation of the radiality constraint was presented in the literature. Therefore, the proposal of this work is to present mathematical formulations for exact solving of the restoration problem of distribution systems operating in radial topology. Two different mathematical formulations are essentially proposed: the first proposal addresses the restoration problem with a simplified approach, where some constraints of the problem are relaxed; and the second proposal addresses the restoration problem with a full approach, where all the fundamental constraints related to technical and operational requirements of the distribution electrical system are considered. The mathematical models can be solved using efficient commercial solvers, appropriate to the type of problem that was formulated in each proposed approach. In this work, mathematical models have been implemented in the mathematical programming environment AMPL and solved ...